Payment by results vs. costs of 24-hour standby in hospitals: evidence from Poland - Raulinajtys-Grzybek. Monika; Świderska, Gertruda Krystyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The purpose of the article was to identify the costs associated with hospital’s standby and to define methodology of calculating and reporting these costs. Standby costs were defined as the costs of the provision of 24-hour access to health care in hospitals. Reimbursing standby costs on the basis of their costs would complement the Payment by Results model. The costing model for calculation of standby costs has been designed and subjected to empirical verification. The constructive approach method was used for this purpose and the verification process took place in 11 hospitals in the area of obstetrics. The obtained results demonstrate the practical applicability of the designed methodology
Argumenta Oeconomica, 2015, Nr 2 (35), s. 85-104
Keywords: cost-based pricing; healthcare; costing model; standby costs; Payment by Results